Analisis Data Antrean Non-Poisson : Studi Kasus: Konsumen Toko Ritel Indomaret Jimbaran - Ni Putu Linda Maharani; Ni Putu Meyla Aryani; Anak Agung Ngurah Bagus Surya Ananta Jelai; Made Ayu Dwi Octavanny (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Queues are a common phenomenon and are often encountered in various aspects of daily life, especially in places that provide public services. One of the places that is inseparable from the queue problem is Indomaret Jimbaran, Bali. The large number of buyers who send data to Indomaret Jimbaran during peak hours causes the queue rate to be high. This is due to the limited number of service facilities and the time provided to serve each visitor is limited so that the cashier cannot serve buyers optimally. Therefore, the researcher is interested in researching whether the service facilities provided by Indomaret Jimbaran are effective and efficient so that they can satisfy customers.Using the Kolmogorov-Smirnov test, it was found that the appropriate distribution for the interarrival time of customers is the Gamma distribution, while the service time follows the 3-parameter Weibull distribution. The queueing model used is . The results show that having three cashiers is sufficient to handle the level of customer traffic at Indomaret Jimbaran retail store.